Assessing the Efficacy of Peer Teaching as an Alternative to Teaching Practice: A Case of Molepolole College of Education - Kgwefane , Tshepo A.; Masimega, Gosiame Setogile (Journal of Education and Practice, 2023)
Purpose: The study sought to assess the effectiveness of peer teaching as a replacement of school-based teaching practice. Methodology: The study used a case study research design and applied mixed methods approach to evaluate the viability of peer teaching as an option for school-based teaching practice. Questionnaires, interviews and group discussions were used to collect data. Different participants were randomly selected to respond to a questionnaire and they comprised sixty (60) year 3 students and sixty (60) lecturers. Ten (10) lecturers including four (4) Heads of Departments were purposively selected for interviews while six (6) student teachers were conveniently selected for group discussions. Findings: The results indicated that peer teaching is a useful strategy to introduce teacher interns to the art of teaching. However, the peer teaching practice environment does not represent the realities of the school classroom. Thus, peer teaching is inadequate to be used as a substitute for school based teaching practice. The results point to need for a thorough review of the use of peer teaching in place of the school-based teaching practice. Unique contribution to theory, practice and policy: Pedagogical content knowledge remains key form of knowledge in teacher professional development. The comparative study findings affirm the utility of the two strategies of peer teaching and teaching practice in teacher professional development. It highlights the limitations of peer teaching and underscores the uniqueness of teaching practice. Thus, it cautions against the use of peer teaching as a replacement for the traditional school-based teaching practice. This challenges both practitioners and policy makers to think of alternative practices to be used instead of teaching practice in the event the usual experiential on-field practice option is not available.